Nonlinear Control of a Buck Converter Which Feeds a Constant Power Load - Solsona, Jorge Alberto (2015)
In this paper a non-linear control strategy for controlling a dc/dc Buck converter feeding a constant power load is proposed. The main objective of the proposed controller is to improve the transient performance when in presence of unknown power disturbances. A feedback controller is combined with a feedforward strategy. A non-linear reduced order observer is used for estimating the value of the power load and its time derivative. These estimated values are fed forward to the non-linear feedback controller whose design is based on feedback linearization method. The proposed controller is tested via simulation and experimental results.